HUBUNGAN BEBERAPA FAKTOR DETERMINAN DENGAN KUALITAS DATA ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RUMAH SAKIT UMUM KOTA BEKASI TAHUN 2015 - Wulandari, Rani Indah (Jurnal Kesehatan Masyarakat (Undip), 2016)
The completeness and timeliness are two of indicator to asses data quality. In RSUD Bekasi there are still incomplete of inpatient medical record on April 2015 (21.25%) and the resending of obstetric medical record still not on time on Juni 2015 (74.08%).The purpose of this study is to analyze the corelation between several determinant factors with data quality of nurse’s care documentation in inpatient of RSUD Bekasi. The method used was Explanantory Research with Cross Sectional Study. Population research was 62 nurses who work in inpatient instalation in the morning and the sample was total population. Data analysis consisted of univariate (performance index) and bivariate (correlation Rank Spearman). Results of univarate analysis showed the performance index of knownledge (77%), skill (71%), intrinsic motivation (79%), extrinsic motivation (71%), supervision(80%), reward (75%), resources (65%), dan complexity of form (72%), the complete of data nurse’s care document(64.29%), and the resending of nurse’s care documentation(44%). Bivariate analysis showed that there are a correlation between independent variable with data quality of nurse’s care documentation, very weak (negative) is reward (rs= -0.051); very weak (positive) are intrinsic motivation(rs=0.160), supervision (rs=0.092), the complexity of form (rs=0.088);and weak corelation (positive) are knownledge(rs=0.283), skill(rs=0.292), extrinsic motivation(rs=0.269) and resources(rs=0.291). Recommendation to RSUD Bekasi are establish a program about education and training to enhance the competence of nurse’s and the nurse’s should be actively participate in training and active discuss with the head of the room.